ENT 530 : Case Study: Theklasickl / Nurlaila Ruselan ... [et al.] - Ruselan, Nurlaila; Ahmad Hafidz, Saza Najiha; Zainuddin, Nur Atikah; Mohamed Nazim, Rasyiqa; Zulkafli, Nur Ain Nabihah (2021)
The main of this report was assigned to a company that operates a business of selling women's clothing such as Baju Kedah with variety of design and to complete our group assignment, our group has decided to choose Theklasickl. We have gone to interview Miss Farisha Naziera who is the owner of Theklasickl. Why we choose this entrepreneurship compared to another entrepreneurship? Because we can see the potential and recognize some issues in the operation that be solved, leading to a better performance than the current one. The case study describes the client’s business objective, how to overcome the business problem? The best solution? And how that solution benefited the client’s corporate efficiency, marketing strength or sales numbers. The main issue that we would like to bring up is a lack of time management. As a partnership entrepreneur who is still working and studying, it is difficult to find time for them to create content, edit videos, photoshoots for the best photos to promote their products in a more interesting way and the time required to complete all of those is very exhausting. They need to make this business idea work and that involves marketing to their prospects so that they can make sales. Other than that, business stocks are limited to a certain amount at a time. Some of the challenges are also related to existing stock, such as when stock for a particular design and size is out of stock and it takes several days or even weeks for it to become available again. Furthermore, we begin by assessing the company's position using a SWOT (Strength, Weakness, Opportunity, Threats) analysis. This analysis is important because it will guide our study in observing the problem and finding an alternative for the business that could overcome the issue through proper analysis of the pros and cons of each alternative, thus deciding which one to apply for the business. It is assumed that if the problem is resolved, the company's performance will improve beyond its current level.